1953
DOI: 10.1017/s0021859600044580
|View full text |Cite
|
Sign up to set email alerts
|

The partition of carotenoids and vitamin A in the colostrum and milk of the cow and the goat

Abstract: The partition of carotenoids and vitamin A in the colostrum of nine cows and six goats and in the milk of three cows and two goats was determined using chromatographic and spectrophotometric methods. The following were the main results:1. The content of β-carotene and vitamin A in the colostrum decreased rapidly during the first nine milkings in both the cow and the goat. The rates of decline were logarithmic. Logarithmic regressions also showed that the decreases in β-carotene were more rapid than those of vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
7
0

Year Published

1953
1953
1984
1984

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 44 publications
3
7
0
Order By: Relevance
“…This agrees with the earlier finding of the present author (Chanda, 1953) that the vitamin A content of cow and goat milk fat, in contrast to that of the carotenoids, continues to change throughout lactation. In these earlier experiments Chanda (1953) showed that variations in the ratio ofvitamin A/g. fat to ,B-carotene/g.…”
Section: I953supporting
confidence: 94%
See 2 more Smart Citations
“…This agrees with the earlier finding of the present author (Chanda, 1953) that the vitamin A content of cow and goat milk fat, in contrast to that of the carotenoids, continues to change throughout lactation. In these earlier experiments Chanda (1953) showed that variations in the ratio ofvitamin A/g. fat to ,B-carotene/g.…”
Section: I953supporting
confidence: 94%
“…4) or are induced artificially by hormones (Chanda et al 1952) or are produced naturally during declining lactation (Chanda & Owen, 1952b). The inverse relationship between phosphatase and phosphorylated thiamine has also been demonstrated in human milk ) and in goat milk (Chanda, 1951). Phosphatase (phenol units) Fig.…”
Section: I953mentioning
confidence: 68%
See 1 more Smart Citation
“…Exophthalmus, muscular inco-ordination and diarrhoea were other symptoms of the extreme deficiency. This is apparently because only the ester form of vitamin A in the blood reflects the carotene intake, as Chanda (390) in these laboratories showed for grazing animals and as Chanda et al showed in further experiments. Eaton et al (371,375) found that artificially dried and pelleted hay maintained liver stores better than artificially ground hay, which in turn was better than field-cured hay.…”
Section: Transformation Of Carotene Into Vitamin Amentioning
confidence: 77%
“…In determining the carotenoids and vitamin A in the colostrum and milk of the cow and the goat, Chanda (390) found vitamin A alcohol in cow's milk and in goat's colostrum but not in goat's milk. Though most of the vitamin A in cattle blood was in the form of the alcohol, and though vitamin A alcohol in the blood of the cow tended to be constant the ester varied from cow to cow and from time to time in the same cow.…”
Section: Transformation Of Carotene Into Vitamin Amentioning
confidence: 99%